2022
DOI: 10.3847/1538-4357/ac96ed
|View full text |Cite
|
Sign up to set email alerts
|

Magellan/IMACS Spectroscopy of Grus I: A Low Metallicity Ultra-faint Dwarf Galaxy*

Abstract: We present a chemodynamical study of the Grus I ultra-faint dwarf galaxy (UFD) from medium-resolution (R ∼ 11,000) Magellan/IMACS spectra of its individual member stars. We identify eight confirmed members of Grus I, based on their low metallicities and coherent radial velocities, and four candidate members for which only velocities are derived. In contrast to previous work, we find that Grus I has a very low mean metallicity of 〈[Fe/H]〉 = −2.62 ± 0.11 dex, making it one of the most metal-poor UFDs. Grus I has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 118 publications
0
20
0
Order By: Relevance
“…The first published results from this program analyzed Eridanus II (Eri II), the brightest galaxy observed by this program. Specifically, Fu et al (2022) demonstrated that the HST CaHK photometric metallicities are in good agreement with the calcium triplet (CaT) calibration (Li et al 2017) that is the current community standard for ground-based spectroscopic studies characterizing UFDs (Kirby et al 2015;Li et al 2018;Longeard et al 2018;Fritz et al 2019;Simon et al 2020;Chiti et al 2022), as well as its agreement with less-often used photometric metallicity calibrations such as those from RR Lyrae stars (Martínez-Vázquez et al 2021). The well-populated HST-based MDF served as a basis for demonstrating that the star formation of Eri II was characterized by strong outflows and low star formation efficiency (Sandford et al 2022), which are in good agreement with theoretical expectations (Muratov et al 2015).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The first published results from this program analyzed Eridanus II (Eri II), the brightest galaxy observed by this program. Specifically, Fu et al (2022) demonstrated that the HST CaHK photometric metallicities are in good agreement with the calcium triplet (CaT) calibration (Li et al 2017) that is the current community standard for ground-based spectroscopic studies characterizing UFDs (Kirby et al 2015;Li et al 2018;Longeard et al 2018;Fritz et al 2019;Simon et al 2020;Chiti et al 2022), as well as its agreement with less-often used photometric metallicity calibrations such as those from RR Lyrae stars (Martínez-Vázquez et al 2021). The well-populated HST-based MDF served as a basis for demonstrating that the star formation of Eri II was characterized by strong outflows and low star formation efficiency (Sandford et al 2022), which are in good agreement with theoretical expectations (Muratov et al 2015).…”
Section: Introductionmentioning
confidence: 82%
“…We note a few difficulties of relying on spectroscopic velocities for cleaning our entire sample: (i) The on-sky footprint of spectroscopic studies extends beyond our HST field of view and the target density for spectroscopy is smaller due to limitations in slit and fiber placement; (ii) The stars observed spectroscopically are often much brighter than the stars in our sample; and (iii) The brightest stars observed by spectroscopy are often missing from our data due to saturation effects in the archival broadband HST data. Using kinematic information, we were able to remove a total of 8 contaminants: six contaminants in Seg 1 (Simon et al 2011), 15 one contaminant in Ret II (Simon et al 2015), and one contaminant in Grus I (Chiti et al 2022). Some stars in the 13 UFDs we present in this work have been studied via spectroscopy, and 10 of our UFDs have at least some stars in common with spectroscopic studies.…”
Section: Member Selectionmentioning
confidence: 91%
See 1 more Smart Citation
“…We do, however, have multiepoch data by comparing observations in this work to older GMOS data that can be used to detect the presence of further binaries using methods from Minor et al (2010). We note many UFDs have had binary stars identified with multiepoch data (e.g., Carina II, Grus I, and Grus II; Li et al 2018b;Simon et al 2020;Chiti et al 2022) which has led to an inflated velocity dispersion in some other dwarf galaxies (e.g., Triangulum II; Kirby et al 2015aKirby et al , 2017Buttry et al 2022).…”
Section: Literature Comparison In Spectroscopic Membersmentioning
confidence: 97%
“…Understanding the kinematics and chemical composition of UFDs can be approached using photometry and astrometry such as in Pace et al (2022), which prioritizes large samples of data but is limited by reduced precision. Alternatively, spectroscopy generally offers a much deeper analysis with significantly increased depth and accuracy, with the limitation of a reduced sample size of observed member stars (Li et al 2017;Simon et al 2017;Chiti et al 2022;Cerny et al 2023). Furthermore, spectroscopy can be used to gain insight into the nature of unclassified satellites as either a UFD or globular cluster (GC) through kinematic and chemical analysis.…”
Section: Introductionmentioning
confidence: 99%